Nazi Germany : confronting the myths - Epstein, Catherine 1962- (Wiley short histories, 2015)
Preface -- Germany before 1933 -- Hitler and the Nazi movement -- The Nazi party-state -- The racial state -- Nazi Germany in the 1930s : a popular regime? -- War and occupation, 1939-1941 -- Genocide -- Total war, 1942-1945 -- Epilogue